2023
DOI: 10.3390/cells12060952
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ARID1A-Deficient Cancers: An Immune-Metabolic Perspective

Abstract: Epigenetic remodeling and metabolic reprogramming, two well-known cancer hallmarks, are highly intertwined. In addition to their abilities to confer cancer cell growth advantage, these alterations play a critical role in dynamically shaping the tumor microenvironment and antitumor immunity. Recent studies point toward the interplay between epigenetic regulation and metabolic rewiring as a potentially targetable Achilles’ heel in cancer. In this review, we explore the key metabolic mechanisms that underpin the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…In line with our data, ARID1A mutation was found to be associated with increased immune activity in other gastrointestinal (GI) cancers, including the enrichment of CD8 + T cells, NK cells and immune-promoting M1 macrophages [33]. In addition, many studies have reported that ARID1A deficiency correlates with microsatellite instability (MSI), genomic features of GI cancers [15]. A high MSI status is known to confer high immunogenic activity in cancer and improve responsiveness to immunotherapy [16].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In line with our data, ARID1A mutation was found to be associated with increased immune activity in other gastrointestinal (GI) cancers, including the enrichment of CD8 + T cells, NK cells and immune-promoting M1 macrophages [33]. In addition, many studies have reported that ARID1A deficiency correlates with microsatellite instability (MSI), genomic features of GI cancers [15]. A high MSI status is known to confer high immunogenic activity in cancer and improve responsiveness to immunotherapy [16].…”
Section: Discussionsupporting
confidence: 87%
“…Tumor-infiltrating T cells are the determinants of immune tolerance and surveillance in tumors [13]. Studies have shown that ARID1A mutations play a role in the tumor immune phenotype, T cell immunity and the tumor immune microenvironment [14][15][16]. However, the functional implications of ARID1A mutations in the anti-tumor immune response in EAC remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Chidamide is one of the histone deacetylase inhibitors, which selectively inhibits histone deacetylase (HDAC) 1, 2, 3, and 10. [6] Chidamide was approved in December 2014 by the China Food and Drug Administration for the treatment of relapsed or refractory PTCL. [6] However, due to the rare occurrence of SPTCL, there are currently few reports on the treatment of SPTCL with Chidamide.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Chidamide was approved in December 2014 by the China Food and Drug Administration for the treatment of relapsed or refractory PTCL. [ 6 ] However, due to the rare occurrence of SPTCL, there are currently few reports on the treatment of SPTCL with Chidamide. Only 1 case has reported that Chidamide performs well in the treatment of refractory SPTCL.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, such tumors are susceptible to therapy with immune checkpoint inhibitors (McKean et al, 2020). Lebedev et al (2023) investigated the mechanisms underlying the immunomodulatory role of AT-rich interaction domain 1A (ARID1A). ARID1A is the most frequently mutated epigenetic regulator among all human malignancies.…”
Section: Mechanisms Of Resistance Associated With Tumor Propertiesmentioning
confidence: 99%